Effect on Patient Safety of a Resident Physician Schedule Without 24-Hour Shifts. Issue 11 (November 2020) - Landrigan, Christopher P.; Rahman, Shadab A.; Sullivan, Jason P.; Vittinghoff, Eric; Barger, Laura K.; Sanderson, Amy L.; Wright, Kenneth P.; O'Brien, Conor S.; Qadri, Salim; St Hilaire, Melissa A.; Halbower, Ann C.; Segar, Jeffrey L.; et al.
Abstract : (Abstracted from N Engl J Med 2020;382:2514–2523) Over the last 4 decades, a body of literature has studied the effect of extended shifts (working ≥24 hours) for resident physicians on their alertness and performance, and by extension, patient safety. Since then, the results of further studies have been inconsistent.